Experimental performance of polymeric air-solution contactors for liquid desiccant systems. (5th July 2017) - Prieto, Juan; Ortiga, Jordi; Coronas, Alberto
Highlights: Two absorbers of a liquid desiccant system are experimentally evaluated. Absorbers are made of polypropylene; one of them is subject to a plasma treatment. Air flow and solution temperature are the variables that most affect its performance. Plasma treatment on polypropylene enhances the absorber performance. Abstract: This paper evaluates the experimental performance of two falling-film absorbers with horizontal tubes of a liquid desiccant system. Both absorbers are made of polypropylene in order to avoid corrosion when the LiCl-H2 O solution is in contact with them. To improve their wettability, and hence the heat and mass transfer, the tubes from one of the absorbers are subject to a plasma surface treatment. According to the experimental results, the inlet liquid desiccant temperature and air velocity are the variables that most affect the absorber performance. Therefore, these two variables can be used to control the supply humidity ratio and air cooling rate in a liquid desiccant system. Furthermore, in comparison with the absorber with untreated tubes, the absorber with treated tubes performed better in terms of the overall heat transfer coefficient (up to 54 %), the absorber heat duty (about 17%), the air cooling rate (up to 29%) and the dehumidification rate (20%).